Young Drug Addicts’ Perceptions on Family Relations:The Case of Esenler - Bağcılar, Istanbul - Yaman, Ömer Miraç (Addicta: The Turkish Journal on Addictions, 2014)
In recent years, there has been a significant increase in drug use and addiction in Turkey, especially among young people aged 15-25. This study focused on young drug addicts and their families, examining young drug addicts’ perceptions about family relationships. Using qualitative research methods, data were collected from 10 young people as well as 2 individuals who do not use drugs and who reside in the same neighborhood through semi-structured interviews. The data were processed using a descriptive analysis according to predefined themes. The findings of the study revealed that the problems young people face with their families may either trigger or increase current substance abuse. A troubled relationship with parents is also a basic determinant of such behaviors as running away from home or a tendency to commit crimes in young people. In addition, if a young individual’s substance abuse is noticed by parents, family relationships face may become even more strained. It was observed that parents exert a high level of influence over their children both during and after adolescence, and that genuine communication with young people was found to be an important factor in their choice to refrain from substance use.
Keywords: Drug addiction; Substance abuse in youth; Family relations